The Impact of Value and Growth Investment Strategies on Initial Underpricing and Long-Run Underperformance of Initial Public Offerings: Empirical Study with Finnish IPOs 1994–2006 - Hahl, Teemu (My University, 2010)
The purpose of this thesis was to study the performance of value and growth investment strategies with Finnish IPOs by classifying the IPOs into value, neutral and growth subgroups according to their B/M. Simultaneously, the aftermarket behavior of IPOs as a whole was examined. Empirically motivated hypotheses stated that growth IPOs are the most underpriced and outperform value IPOs in the short-run up to 6 months after the issue, whereas value IPOs underperform less in the long-run than growth IPOs. The sample consisted of 67 IPOs issued between 1994 and 2006 in the Helsinki Stock Exchange. The short-run performance was examined with the 1st day, 1-month, 3-month and 6-month return horizons in a market-adjusted framework and on a 6-month risk-adjusted basis. The long-run performance was in turn investigated with market-adjusted return intervals of 1, 2 and 3 years after the issue and on a 3-year risk-adjusted basis. The risks taken into account were beta and size. Finally, market-adjusted returns were calculated with both the 1st day excluded and included. The empirical results indicated no significant differences in initial returns that were substantially positive on average. However, the findings suggested that value IPOs have been underpriced, whereas growth IPOs have been overpriced. Moreover, a market-adjusted short-run growth premium was found, but it was compensation for higher risk exposure. Finally, a substantial long-run value premium was detected, which became even stronger after risk adjustments. The results indicated that the value effect was driven by the poor performance of growth IPOs that also caused the underperformance of IPOs as a whole. The evidence strongly supported the behavioral theories on value effect as it was mainly caused by irrational early aftermarket overpricing of risky growth IPOs. Furthermore, it was found that IPO underperformance is not a distinct anomaly, but a manifestation of the cross-sectional attributes of the issuing firms.
Keywords: Value; growth; investment strategies; B/M; initial public offering; IPO; underpricing; underperformance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|